Responses of tomato plant growth and root-knot nematodes to phytonematicides from fermented fresh fruits of two indigenous cucumis species - Tseke, Pontsho Edmund (University of Limpopo, 2013)
Two phytonematicides were researched and developed from fermented crude extracts of wild watermelon (Cucumis africanus) and wild cucumber (Cucumis myriocarpus) fruits for use as alternatives to methyl bromide in managing root-knot (Meloidogyne species) nematodes in tomato (Solanum lycopersicum) production. Fruits of C. africanus contain cucurbitacin B (C32H48O8), while those of C. myriocarpus contain cucurbitacin A, which comprises cucumin (C27H40O9) and leptodermin (C27H38O8). Phytonematicides from C. africanus and C. myriocarpus fruits are referred to as nemafric-B and nemarioc-A, respectively. The two phytonematicides, due to their origin from plant species with allelochemicals, have high potential of being phytotoxic to crops. The use of the Curve-fitting Allelochemical Response Dosage (CARD) computer-based model assisted in the establishment of concentrations which were stimulatory to growth of tomato (Solanum lycopersicum) plants, while exhibiting nematoxic properties to Meloidogyne species. The two phytonematicides were developed from crude extracts of fruits dried at 52˚C in air-forced ovens and ground in a Wiley mill through 1-mm-opening sieves. However, equipment for drying and grinding fruits would not be accessible to smallholder farmers who wished to prepare their own products on-farm. The objective of this study therefore, was to determine whether nemafric-BL and nemarioc-AL produced from fresh fruit of the two Cucumis species would be suitable for use (i.e. non phytotoxic) in tomato production for managing population densities of M. incognita race 2. In order to distinguish the products of fresh (F) fruits from those of dried (D) fruits, they were code-named nemafricF-BL or nemariocF-BL and nemafricD-BL or nemariocD AL, respectively, where G and L denoted granular and liquid formulations, respectively. Tomato cv. ‘Floradade’ seedlings were infested with 3 000 eggs and second-stage xv juveniles of M. incognita race 2. An equivalent of 40 g and 80 g dried fruit mass of nemafric-B and nemarioc-A, namely, 284 g and 411 g fresh fruit mass for nemafric-B and nemarioc-A, respectively, were separately fermented using EMROSA effective micro-organisms mixed with 16 L chlorine-free tapwater in 20 L container for 14 days at ± 25˚C, allowing pH to gradually decline to ± 3.7. Separate experiments for each product run concurrently. Treatments, namely, 0, 2, 4, 8, 16, 32 and 64% concentrations, where for instance, 2% = 20 ml/1000 ml x 100, were arranged in a randomised complete block design, with 10 replications. Blocking in the greenhouse was done for wind direction which was regularly erected by fans for cooling down the greenhouse. At 56 days after weekly application of each treatment, flower number, fruit number, dry shoot mass, dry root mass, dry fruit mass, plant height, stem diameter and nematode numbers were each subjected to analysis of variance. Nematode data were, prior to analysis, transformed using log10(x + 1), but untransformed data were reported. Using the sum of squares, nemafric-BL and nemarioc-AL treatments affected dry root mass, dry shoot mass, flowers number, fruit number, plant height and stem diameter. Nemafric-BL contributed 67%, 78%, 58%, 43%, 60% and 26%, while nemarioc-AL contributed 71%, 61%, 19%, 35%, 34% and 24% to total treatment variation of the six respective variables. Plant variables with significant (P ≤ 0.05) treatment effects were further subjected to the CARD model to generate seven biological indices, with three distinct phases, namely, stimulation, neutral and inhibition phases. Using the quantified stimulation phase, the mean concentration stimulation range (MCSR) was computed for each variable using two biological indices, namely, threshold stimulation point (Dm) and saturation point (Rh). The CARD model explained 98%, 99%, 98% and 98% of the quadratic models of dry root mass, dry shoot mass, plant height and stem diameter, xvi respectively, against increasing concentrations of nemarioc-AL. Similarly, the CARD model explained 99%, 96%, 84% and 93% of total treatment variation in the respective plant variables. The integrated MCSR [MSCR = Dm + (Rh/2)] for nemafric-BL on tomato plants was 7%, while that for nemarioc-AL was 4%. In the CARD model, the overall sensitivities (∑k) of tomato plants exposed to nemafric-BL and nemarioc-AL were 3 units and 5 units, respectively. Tomato plants were therefore, less sensitive to nemarioc-AL since it had higher ∑k value than nemafric-BL. At 4% nemarioc-AL and at 7% nemafric-BL, the two phytonematicides were each highly suppressive to population densities of M. incognita race 2. In conclusion, on the basis of non-phytotoxicity of the computed MCSR values and their suppressive effects on population densities of M. incognita race 2, the smallholder farmers could produce nemafric-BL and nemarioc-AL phytonematicides on-farm. However, the production of the two products from fresh fruits would not be sustainable since fruits of the two Cucumis species are highly seasonal due to the high incidence of post-harvest decays.
Thesis (M.Sc. (Plant Production)) -- University of Limpopo, 2013
Keywords: Root-knot nematodes; Phytonematicides; Fermented fresh fruits; Indigenous cucumis species; Nematocides; Tomatoes-Breeding; Cucumis